2022
DOI: 10.3390/math10234497
|View full text |Cite
|
Sign up to set email alerts
|

Could Religiosity and Religion Influence the Tax Morale of Individuals? An Empirical Analysis Based on Variable Selection Methods

Abstract: When people who adhere to tax morality act in a situation where there is no sense of risk, no acceptance of the government, or no environment conducive to tax compliance, it is easier to see how they are motivated to do so. Tax morality is also known as the ethics of compliance. It is the independent cause that motivates a positive tax behaviour. Employees’ religious beliefs may impact their ideas and actions in organizational life, just as individuals’ attitudes, values, emotions, abilities, and behaviours in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
2
0
1
Order By: Relevance
“…Dibandingkan dengan para penganut barat, penganut Tao dan Budha memiliki ketertarikan yang lebih kuat dalam hal kegiatan dan kepercayaan terhadap agama (Shiah et al, 2013;Davidescu et al, 2022) Schneider, 2011).…”
Section: Perspektif Budha Dalam Perpajakanunclassified
“…Dibandingkan dengan para penganut barat, penganut Tao dan Budha memiliki ketertarikan yang lebih kuat dalam hal kegiatan dan kepercayaan terhadap agama (Shiah et al, 2013;Davidescu et al, 2022) Schneider, 2011).…”
Section: Perspektif Budha Dalam Perpajakanunclassified
“…So that the hypothesis formulation is: H1: Money ethics has a positive relation tax evasion. (Davidescu et al, 2022) argued, tax morale is the motivation of a country's citizens to pay taxes without the help of any legal obligations. Tax morale is a motivation for taxpayers so that they are aware of their obligation to pay taxes.…”
Section: Planned Of Behavior Theory Money Ethics and Tax Evasionmentioning
confidence: 99%
“…The second factor is tax morale. One of the first studies in the tax morale literature was conducted by (Davidescu et al, 2022) He explained tax morale as the attitude of a group or the entire population of taxpayers towards the issue of fulfilling or ignoring their tax obligations; tax morale is embedded in the tax mentality of citizens and their awareness as citizens, which is the basis for their inner acceptance of tax obligations and recognition of state sovereignty (Parwati et al, 2021) Previous research (Owusu et al, 2022) confirmed that tax morale is one of the factors that have a negative impact on tax evasion. In other words, tax morale is the taxpayer's perception of tax evasion.…”
Section: Introductionmentioning
confidence: 99%